The Limola Language and Its Syntax: Unveiling the Functions, Structure, and Categories - Yulianti, Andi Indah; Hidayah, Asri M. Nur; Wibowo, Agus Hari; Maharani, Amanda Vira; Septiana, Dwiani; Rosni, Darmawati Majid (Indonesian Journal of EFL and Linguistics, 2024)
Investigating the linguistic system of a regional language offers significant advantages from both the linguistic and cultural conservation perspectives. By examining a language's linguistic system, researchers can identify specific patterns employing subjects, verbs, objects, and other sentence elements while also documenting and preserving the language. Analyzing the syntax of the Limola language can provide new insights into general syntactic theory. The purpose of this study was to describe the syntactic functions, categories, and roles of Limola using a syntactic typology approach, clearly illustrating its syntactic functions, categories, and roles. The data for this study comprised phrases, clauses, and sentences in the Limola language, collected through instruments completed by sources and informants from two villages: Sassa and Makumpa. Data collection methods involved observation (survey), elicitation, and documentation. In drawing conclusions and discussions, triangulation presents the findings based on relevant theories. The results indicate that the syntactic categories in Limola are divided into five main categories: verbs, adjectives, adverbs, nouns, and numerals, as well as two categories of function words, namely prepositions/conjunctions and pronouns. Each category plays a vital role in shaping Limola`s meaning and sentence structure.